Measurement of Physical Dimensions of Mung Bean - Ravikanth, L.; Jayas, D. S.; Alagusundaram, K.; Chelladurai, V. (Journal of Agricultural Engineering, 2014)
Physical dimensions of mung bean (Vigna radiate) are essential to design equipment for handling, conveying, separation, drying, aeration, storage and processing of mung bean. Physical dimensions (area, perimeter, maximum radius, minimum radius, mean radius, major axis length and minor axis length) were measured as a function of moisture content in the range of 9.9 to 18.3% w.b. using digital image processing technique. Four hundred and fifty individual kernels were selected randomly for each moisture content and colour image of individual kernels using a digital camera. Of the seven morphological features analyzed, four features (area, perimeter, maximum radius and mean radius) of mung bean were significantly (Î±=0.05) different at different moisture contents. These four features increased linearly with increase in moisture content of grain. Minimum radius and length of the mung bean kernel did not show significant change (Î± = 0.05) with increase in moisture content from 9.9 to 18.3% w.b.